2015
DOI: 10.1186/s12909-015-0404-4
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of medical student resilience in longitudinal integrated clerkships

Abstract: BackgroundResilience is required to succeed academically, overcome challenges during clinical training and cope positively with stress in future professional life. With medical students at high risk of mental illness, socially accountable medical schools are seeking to foster student resilience. This exploratory study proposes a conceptual framework for student resilience in longitudinal integrated clerkships (LICs).MethodsThis qualitative study sought to understand student resilience during the first year of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 31 publications
0
33
0
1
Order By: Relevance
“…Previous studies have reported the importance of continuity of care from the medical school in providing a supportive and stable environment for students [27]. Given medical school curricula are split between early years and later years and medical students are dispersed at various sites along their training, establishing continuity of care remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the importance of continuity of care from the medical school in providing a supportive and stable environment for students [27]. Given medical school curricula are split between early years and later years and medical students are dispersed at various sites along their training, establishing continuity of care remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The opposite also held; those who related positive experiences described them as supportive of wellbeing. Previous research has shown that student perception of support and interest in students' education by faculty is associated with increased odds for recovery from burnout [25], and clinical supervisors can serve as sources of stability and continuity for medical students [48]. Our findings suggest that mutually trusting relationships between staff and students could promote wellbeing per se, as well as enhance engagement and uptake of wellbeing initiatives.…”
Section: Staff Attitudes Towards Studentsmentioning
confidence: 55%
“…The year 4 results suggest that spending a year rurally and reintegrating into the mainstream encouraged the development of resilience and is reassuring as it suggests that the geographical and academic isolation that can be part of rural placement has not shown negative effects on students’ resilience. This is supported by qualitative research by a study examining the development of resilience during a long‐term rural placement.…”
Section: Discussionmentioning
confidence: 98%